PERPUSTAKAAN ELMULOKA DALAM MENDUKUNG LITERASI ANAK MELALUI LAYANAN DAN PROGRAM KREATIF - Hanifah, Jezzyndah; Chantika Sari, Ananta; Fadiyah Hadinah, Dewi; Dinanti, Raina; Silvana, Hana; Yanti Ramadhan, Suci (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2025)
Children's library services play a crucial role in fostering literacy, creativity, and a lifelong interest in learning from an early age. Through safe spaces, age-appropriate collections, and educational and digital programs, libraries such as Elmuloka support children's growth and development holistically and inclusively. Knowing the quality of children's information services in libraries is important as a basis for developing and improving services. This study aims to identify the information needs of children and the most effective approach to delivering children's services. This study uses qualitative research by conducting observations and interviews with librarians and users of the Elmuloka Library in Bandung. The reading sources available at the Elmuloka library include fiction, and non-fiction books, and access to children's magazines. The facilities provided are a children's reading room, bookshelves, and a room for storytelling. The service programs presented to increase children's interest in reading are Tuesday play, Wednesday story, little librarians, and book clubs. The interactions provided have met the requirements because librarians always ensure that children are under adult supervision to avoid taking book collections that are not appropriate for the child's age.